1970
DOI: 10.1210/jcem-30-3-345
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Stimulation ofin VitroProgesterone Synthesis

Abstract: Bovine corpora lutea slices were incubated with prostaglandins and gonadotropins. All the prostaglandins tested (PGE 2 , PGE X , PGFjo and PGAi) were found to be steroidogenic, stimulating both the production of progesterone as measured in micrograms and the incorporation of radioactivity from acetate-l-u C. Prostaglandin E2 (PGE 2 ) gave the greatest effect, being approximately half as effective as luteinizing hormone (LH) on a molar basis. There were similarities between gonadotropin and prostaglandin. Cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(39 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…The reason for the immediate positive progesterone response to PGF treatment is not known. Based on an in vitro study (Speroff & Ramwell 1970), a direct PGF steroidogenic stimulation of luteal cells has been suggested (Hixon & Hansel 1974). Direct inhibitory and stimulating effects of PGF on small and large luteal cells respectively have been demonstrated in vitro (Alila et al 1988, Meidan et al 1992, Girsh et al 1995, Okuda et al 1998, Skarzynski & Okuda 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the immediate positive progesterone response to PGF treatment is not known. Based on an in vitro study (Speroff & Ramwell 1970), a direct PGF steroidogenic stimulation of luteal cells has been suggested (Hixon & Hansel 1974). Direct inhibitory and stimulating effects of PGF on small and large luteal cells respectively have been demonstrated in vitro (Alila et al 1988, Meidan et al 1992, Girsh et al 1995, Okuda et al 1998, Skarzynski & Okuda 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the increase or persistence in prostanoid biosynthesis in the late luteal phase is thought to be an important process in initiation of luteolysis. While both PGE 2 and PGI 2 are supposed to be luteotropic in vitro [16], the overall effects of prostanoids during the late luteal phase would be luteolytic. The mechanism by which NDGA affects luteal activity seems to be complex.…”
Section: Discussionmentioning
confidence: 99%
“…It was also concluded from other studies of early (Little et ai, 1982;Roche et ai, 1985) and later (Schallenberger et ai, 1985a;Procknor et ai, 1986) (1985), and PGE-2 (Shemesh et ai, 1979;Shelton et ai, 1990). PGE-2 stimulates progesterone synthesis in dispersed bovine (Speroff & Ramwell, 1970) and ovine (Fitz et ai, 1984) luteal cells in vitro, although its action in vivo is not as clearly defined. Some in-vitro studies have also reported antagonism by PGE-2 of LH-stimulated progesterone synthesis in vitro (Thomas et ai, 1978;Stouffer et ai, 1979;Shelton et ai, 1990).…”
Section: Discussionmentioning
confidence: 99%